The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1186/preaccept-6695611611337601
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of senior hospital managers¿ views on current and innovative strategies to improve hand hygiene

Abstract: Background: Despite universal recognition of the importance of hand hygiene in reducing the incidence of healthcare associated infections, health care workers' compliance with best practice has been sub-optimal. Senior hospital managers have responsibilities for implementing patient safety initiatives and are therefore ideally placed to provide suggestions for improving strategies to increase hand hygiene compliance. This is an under-researched area, accordingly the aim of this study was to identify senior hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 38 publications
(52 reference statements)
1
17
0
Order By: Relevance
“…Kebede et al stated that the establishment of hospital manager training in order to better equip them with management skills may promote scalable improvements in health facility functioning ( 14 ). As senior health care managers play an important role in the design and operationalization of quality improvement programs, they can offer a unique perspective on how to improve areas of practice with which healthcare organizations are often struggling to improve ( 21 ). This study showed that people skills were important for hospital managers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kebede et al stated that the establishment of hospital manager training in order to better equip them with management skills may promote scalable improvements in health facility functioning ( 14 ). As senior health care managers play an important role in the design and operationalization of quality improvement programs, they can offer a unique perspective on how to improve areas of practice with which healthcare organizations are often struggling to improve ( 21 ). This study showed that people skills were important for hospital managers.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of transparency rules and duties and role of managers also were expressed as challenges for hospital management. McInnes et al found that culture change starts with leaders and is one of the main issues that managers have faced in hospitals ( 21 ). Therefore, it is suggested that high-level meetings should be scheduled between the Ministry of Health and university heads at early stages in order to gain leadership support in deploying change.…”
Section: Discussionmentioning
confidence: 99%
“…Hospitals need to come up with innovative ways of monitoring HCWs’ HH performance and provide them with proper feedback. McInnes et al conducted a qualitative study that aimed at understanding the perspectives of senior managers regarding current and future strategies to improve HH compliance [ 9 ]. Alongside several interesting issues mentioned, the need of having individualized and immediate real-time feedback of HH practices must be highlighted.…”
Section: Introductionmentioning
confidence: 99%
“…204 – 206 A study investigating the failure of an HCAIs strategy found low levels of physician engagement and compliance with guidelines and policies. 207 , 208 Even in healthcare facilities where policies, guidelines, and checklists were effectively implemented, doctors and other health professionals’ practices were found to degrade after around one year. The reasons given included: too much information being provided; guidelines being too complicated to implement; that guidelines conflicted with other guidelines, and because little evidence was provided to support the guidance.…”
Section: Methodsmentioning
confidence: 99%